The Membrane-Associated MARCH E3 Ligase Family: Emerging Roles in Immune Regulation - Lin, Heng; Li, Shu; Shu, Hong-Bing (Frontiers in Immunology, 2019)
The membrane-associated RING-CH-type finger (MARCH) proteins of E3 ubiquitin ligases have emerged as critical regulators of immune responses. MARCH proteins target immune receptors, viral proteins as well as components in innate immune response for polyubiquitination and degradations via distinct routes. This review summarizes the current progress about MARCH proteins and their regulation on immune responses.